New finds of antler cheekpieces and horse burials from the Trzciniec Culture in the territory of western Little Poland - Przybyła, Marcin (Analecta Archaeologica Ressoviensia, 2020)
The subject of this paper are the new discoveries of antler cheekpieces of horse harness at Trzciniec Culture sites in Morawianki, Miechow and Jakuszowice (Little Poland, Poland). It also addresses the issue of double horse burials being parts of sepulchral complexes, with barrows at their centres. The article tackles the problem of the occurrence of such burials and cheekpieces in the Danubian regions, the steppe zone of Eastern Europe and in the territory of Greece. It also considers the function of cheekpieces, as parts of horse gear used for harnessing a horse to a chariot.